Soil Water Release Curves : Indicator to Suit Sustainable Cropping Scheme under Sloppy Rain-Fed Climatic Conditions of Pothowar Plateau of Punjab-Pakistan - Rehmat Ullah; Shehzada Munawar Mehdi; Khalid Saif Ullah Khan; Aftab Ahmed Sheikh; Sigit Mujiharjo; Muhammad Saud (Badan Penerbitan Fakultas Pertanian (BPFP), 2018)
In arid environment, limitations of crop productivity could be improved by soil management practices like soil conservation measures, tillage and reducing slopes through terracing on different cropping patterns. These patterns include area as Wheat-Maize (WMCP) and Wheat-Fodder (WFCP) in Kahuta (high rainfall climatic area), Wheat-Millet-Fallow (WMFCP) and Wheat- Millet-Lentil (WMLCP) in Khairimurat (medium rainfall climatic area) and Wheat-Fallow (WFCP) and Fallow-Groundnut (FGCP) in Pindi Gheb (low rainfall climatic area). In areas that have more crop water requirements the yield of these crops has been affected when the drought prevails. Our results evidenced that more average soil water content (ASWC) was available in high to medium height terraces in WMCP and low to medium in WFCP of Kahuta area. ASWC remained more in high to medium height terraces under all cropping pattern of Khairimurat during September. ASWC remained more in low to medium height terraces under all cropping pattern of Pindi Gheb during September and December. Equidistantly, soil water release curve also indicated that medium rainfall sites had more plant water availability as compared to high and low rainfall sites. Yield relationship to plant water availability revealed significance for intrusion of modified cropping patterns rather than existing cropping patterns on sustained basis. Finally, our study suggests that cropping patterns of high and low rainfall areas should adjusted by growing low water requirement crops in summer seasons to cope the drought period for the sustainability of agriculture under rainfed climatic conditions. Keywords : cropping patterns, Pothowar Plateau, soil water contents, soil water release curve, sloppy lands